Peritonitis and Necrotizing Hepatitis in Ara ararauna Caused by a Foreign Body - Justino, Larissa; Menck-Costa, Maisa Fabiana; Xavier, Ana Aparecida Correa; Souza, Marielen de; Santos, Beatriz Queiroz dos; Bracarense, Ana Paula Frederico Rodrigues Loureiro; Baptista, Ana Angelita Sampaio (Acta Scientiae Veterinariae, 2021)
Background: The ingestion of foreign bodies in parrots has already been described and associated with the curious behavior of the birds or with stressful conditions. Foreign bodies in the gastrointestinal tract are usually diagnosed through clinical signs, laboratory tests, and radiographic findings in the historical data. Foreign bodies are usually metallic and can lodge in any segment of the gastrointestinal tract, commonly found in the proventricle and gizzard. This study investigated a case of necrotizing hepatitis due to a foreign body in Ara ararauna (Linnaeus, 1758). Case: An approximately 9-month-old specimen of caninde macaw, had sudden death and was referred for autopsy. The macroscopic examination revealed a fibrous, thick, reddish membrane involving the left hepatic lobe and partially the gizzard in continuity with the peritoneum. Inside the capsule, the liver had a friable and necrotic appearance and the gizzard had a focal perforation area containing a foreign body (gavage probe). We performed the histopathological examination of the liver and gizzard and observed that the membrane surrounding the liver and partially the gizzard had a chronic inflammatory process with a marked proliferation of fibrous tissue and fibrin deposition. The hepatic parenchyma of the left lobe showed diffuse and marked necrosis, with signs of ischemic necrosis. In the region of transmural perforation of the gizzard, the mucosa showed a focal area of extensive necrosis accompanied by the presence of intralesional bacteria. The lesions observed are attributed to the perforation of the organs by the foreign body. It is not known whether the bird ingested the object accidently during food handling as a young or due to the curious behavior of the bird or even the stress it may have been exposed to. The post-mortem examination revealed localized peritonitis and encapsulating necrotizing hepatitis, focally extensive and accentuated, associated with foreign body perforation. Discussion: The curious habit of parrots, can provide the ingestion of foreign bodies, in which they lodge in the gastrointestinal tract. Generally, the clinical signs are nonspecific, however, proventricular impaction, stasis and even perforations in the mucosa of organs can be observed. In the present study, we suspect that the Caninde macaw accidentally ingested a gavage probe during feeding management as a young. This object lodged in the bird's ventricle, perforating the organ and reaching the liver, due to intimate contact with the gizzard, providing a picture of ventriculitis and necrotizing hepatitis. Necrotizing hepatitis due to foreign body has been reported in the literature due to ingestion of perforating foreign body with lesion in the left ventricle and lobe, however we have no knowledge of reports with the presence of a capsule involving the left hepatic lobe, similar to a capsule like this, we understand that our report is the first description of encapsulating necrotizing hepatitis in birds. We believe that this capsule of connective tissue was formed, due to the inflammatory process in the peritoneal cavity, in birds the deposition of fibrin can form a structure similar to a capsule, in order to trap cells and the agent responsible for inflammation, preventing septicemia. Transmural perforation in the gizzard, observed in this case, allowed bacterial translocation that may have contributed to the worsening of the chronic condition and death due to the accumulation of toxins or bacterial translocation of the gastric tract, leading to liver infection and sepsis. We concluded that the presence of the perforating foreign body was responsible for the peritonitis and encapsulating necrotizing hepatitis in Ara ararauna.